Sealed alkaline aluminum air battery activated by adding water

By using low-yield thermal solid electrolyte and waterproof and breathable membrane in aluminum air batteries, a fully sealed structure activated by water is realized, solving the problems of inconvenient use and poor safety of alkaline aluminum air batteries in the prior art, and achieving high voltage, high capacity, safe and convenient battery performance.

CN119695357AActive Publication Date: 2025-03-25DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202311226961.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-22
Publication Date
2025-03-25
Estimated Expiration
2043-09-22

AI Technical Summary

Technical Problem

It is inconvenient to add alkaline electrolyte before use, and a large amount of heat is generated when the solid alkali dissolves, resulting in corrosion of the aluminum electrode and affecting the safety of the battery.

Method used

The low-yield thermal solid electrolyte and waterproof and breathable membrane are used to make the battery work by adding water to activate it, ensuring that the battery has a fully sealed structure and the operator does not contact alkaline electrolyte, which improves safety and convenience.

Benefits of technology

It realizes the high voltage and high capacity of aluminum air batteries, and has the advantages of convenient and safe water activation, avoiding the inconvenience of manually adding alkaline electrolyte before use, and reducing the risk of corrosion caused by heat.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004462630570000011
    Figure HDA0004462630570000011
  • Figure HDA0004462630570000012
    Figure HDA0004462630570000012
Patent Text Reader

Abstract

The sealed alkaline aluminum air battery comprises a battery shell, an aluminum electrode and an air electrode, the aluminum electrode is arranged in the battery shell, the air electrode is arranged at a through hole in the side wall face of the battery shell, and the peripheral edge of the air electrode is connected with the peripheral wall face, at the opening end of the through hole, of the battery shell or the inner wall face of the through hole in a sealed mode. A water injection opening is formed in the top of the battery shell, a sealing cover capable of opening and closing the water injection opening is arranged on the water injection opening, a through hole is formed in the top of the battery shell, a waterproof breathable film is arranged at the position of the through hole and covers the position of the through hole, and the peripheral edge of the waterproof breathable film is connected with the peripheral wall face, at the opening end of the through hole, of the battery shell or the inner wall face of the through hole in a sealed mode. And a solid electrolyte is filled in the battery shell. The aluminum air battery has high voltage and high capacity of an alkaline aluminum air battery, and has the advantages that water is added for activation, an operator cannot contact alkali, and the aluminum air battery is safe and convenient.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of aluminum-air batteries, and specifically relates to a sealed alkaline aluminum-air battery that can be activated by adding water, which solves the problems of inconvenience in use and poor safety of alkaline aluminum-air batteries, while ensuring high voltage and high capacity. Background Art

[0002] Aluminum-air batteries are chemical power sources that use aluminum and oxygen in the air as reactive substances. The negative electrode is generally an aluminum alloy plate, the positive electrode is an air electrode, and the electrolyte is an alkaline aqueous solution or a neutral aqueous solution. The electrochemical equivalent of aluminum is 2.98Ah / g, second only to lithium, and the positive active substance oxygen comes from the air, so aluminum / air batteries have the characteristics of high specific energy. In addition, aluminum is abundant in resources, safe to use, and the reaction products are non-toxic and recyclable, making it an ideal electrode material.

[0003] Aluminum-air batteries using alkaline electrolyte systems have higher discharge voltage and discharge capacity than neutral electrolyte systems. However, alkaline solutions are highly corrosive, and it is extremely inconvenient to add alkaline electrolyte to aluminum-air batteries before use. Pre-burying solid alkali in aluminum-air batteries and adding water to activate the battery before use has become a feasible solution, but the problem is that the solid alkali will generate a lot of heat during the dissolution process, and the aluminum electrode will undergo rapid hydrogen evolution corrosion reaction in the hot electrolyte, which will ultimately affect the safety of the battery. The Chinese patent (CN107017411B) mentions a portable, high-efficiency aluminum-oxygen power battery using potassium hydroxide and cyclodextrin colloidal electrolyte that can achieve water injection.

[0004] The present invention proposes a sealed alkaline aluminum-air battery activated by adding water. Through the low-heat-generating electrolyte pre-embedded technology, the aluminum-air battery only needs to be added with water before working. The aluminum-air battery adopts a fully sealed structure containing a waterproof and breathable membrane. The operator cannot contact the alkaline electrolyte during use. The aluminum-air battery has the characteristics of high safety and easy use. Summary of the invention

[0005] A sealed alkaline aluminum-air battery activated by water, the aluminum-air battery comprises a battery shell, an aluminum electrode, an air electrode, a low-heat-generating solid electrolyte, a waterproof breathable membrane and a water injection port. The low-heat-generating solid electrolyte is a mixture of solid alkali and other salts, and the waterproof breathable membrane can ensure liquid sealing while satisfying battery exhaust.

[0006] The low heat generation solid electrolyte includes four components, component 1 is potassium hydroxide, sodium hydroxide or a mixture of the two, component 2 is potassium stannate, sodium stannate or a mixture of the two, component 3 is one or more of ammonium nitrate, ammonium oxalate, ammonium sulfate, potassium nitrate, potassium oxalate, potassium bromide, sodium nitrate, sodium oxalate, sodium bicarbonate, calcium nitrate, and calcium chloride, and component 4 is deionized water. The mixing method of the low heat generation solid electrolyte is to weigh the four components according to a proportion, melt and mix them at a high temperature, and mechanically crush them after cooling and solidification.

[0007] The waterproof breathable membrane is a multilayer composite membrane of a polytetrafluoroethylene porous membrane and one or more of a polyethylene porous membrane, a polypropylene porous membrane, a polyvinylidene fluoride porous membrane, and a polyethylene terephthalate porous membrane, and has a pore size distribution range of 0.01 μm to 10 μm.

[0008] The content of metal aluminum in the aluminum electrode is greater than or equal to 95%.

[0009] The air electrode comprises a catalyst layer, a current collector and a gas diffusion layer.

[0010] The battery shell is a blend of one or more of ABS, polycarbonate, polypropylene, polyethylene, and nylon. The battery shell, the air cathode, and the waterproof breathable membrane are bonded together or integrally injection-molded by epoxy resin to form a sealed battery cavity.

[0011] Description of implementation effect: Compared with the prior art, the aluminum-air battery in the present invention has the advantages of high voltage and high capacity of alkaline aluminum-air batteries, and can be activated by adding water, the operator does not come into contact with alkali, and is safe and convenient. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 This is a schematic diagram of the structure of the water-activated sealed alkaline aluminum-air battery of the present invention.

[0013] Figure 2 The figure is a top view schematic diagram of the sealed alkaline aluminum-air battery activated by water according to the present invention.

[0014] In the figure, 1 is a battery shell, 2 is a battery cover, 3 is an air electrode, 4 is an aluminum electrode, 5 is a solid electrolyte, and 6 is a waterproof and breathable membrane. DETAILED DESCRIPTION

[0015] The following examples further illustrate the present invention in detail but are not intended to limit the present invention.

[0016] like Figure 1 and 2As shown, a sealed alkaline aluminum-air battery activated by water includes a battery shell of a rectangular shape with an internal cavity volume of 150mL, an aluminum electrode, and an air electrode. The aluminum electrode is placed in the battery shell, and the air electrode is placed at the through hole A on the side wall of the battery shell. The edges of the air electrode are tightly connected to the inner wall of the through hole A. A water injection port is provided at the top of the battery shell, and a sealing cover that can open and close the water injection port is provided on the water injection port. A through hole B is provided at the top of the battery shell, and a waterproof breathable membrane is provided at the through hole B. The waterproof breathable membrane covers the through hole, and the edges of the waterproof breathable membrane are tightly connected to the walls of the battery shell at the opening end of the through hole. A solid electrolyte is filled in the battery shell. Two air electrodes are respectively arranged on the left and right sides of the battery shell, and the aluminum electrode is located between the two air electrodes. The aluminum electrode and the two air electrodes are arranged in sequence with intervals and surfaces parallel to each other; the sealing cover is screwed on the water injection port through a thread.

[0017] Example 1

[0018] The aluminum electrode is a sheet of high-purity aluminum with a length*width=9cm*7cm and a thickness of 1mm. The air electrode is composed of a catalyst layer, a copper mesh and a gas diffusion layer stacked and pressed together, and is a sheet with a length*width=10cm*8cm. The catalyst layer is prepared by mixing manganese dioxide, carbon powder and 40% mass concentration polytetrafluoroethylene emulsion in a mass ratio of 1:5:3 and spraying and drying. The gas diffusion layer is prepared by mixing carbon powder and polytetrafluoroethylene in a mass ratio of 2:1 and hot pressing at 300 degrees Celsius. The solid electrolyte consists of 25g potassium hydroxide, 1.2g sodium stannate, 12g ammonium oxalate and 5g deionized water (the preparation method of the solid electrolyte is: after mixing the four components, melt mixing at a high temperature of 150°C, cooling to room temperature and solidifying, and then mechanically crushing into powder). The waterproof and breathable membrane is a composite membrane of a polytetrafluoroethylene porous membrane and a polyvinylidene fluoride porous membrane (manufacturer: Shanghai Minglie New Materials Co., Ltd., model: X1010), and the average pore size of the pores thereon is 0.1μm. The battery shell is made of ABS plastic, and the battery shell is sealed with the air electrode and the waterproof breathable membrane during one-piece injection molding to form a sealed battery cavity. Before use, add 90mL of water to the aluminum-air battery, tighten the sealing cover on the water inlet, and shake the battery. The battery surface temperature is monitored to be 45°C, the battery shell does not expand, and the waterproof breathable membrane does not leak. The above aluminum-air battery is heated at 10mW / cm 2 The battery is discharged at a low power density until it reaches 0.9V low voltage protection, and the discharge capacity is 45Ah.

[0019] Example 2

[0020] The aluminum electrode is a sheet of high-purity aluminum with a length*width=9cm*7cm and a thickness of 1mm. The air electrode is composed of a catalyst layer, a copper mesh and a gas diffusion layer stacked and pressed together, and is a sheet with a length*width=10cm*8cm. The catalyst layer is prepared by mixing manganese dioxide, carbon powder and 40% mass concentration polytetrafluoroethylene emulsion in a mass ratio of 1:5:3 and spraying and drying. The gas diffusion layer is formed by mixing carbon powder and polytetrafluoroethylene in a mass ratio of 2:1 and hot pressing at 300 degrees Celsius. The solid electrolyte consists of 25g potassium hydroxide, 1.2g sodium stannate, 15g potassium nitrate and 5g deionized water (the preparation method of the solid electrolyte is: after mixing the four components, melt mixing at a high temperature of 150°C, cooling to room temperature and solidifying, and then mechanically crushing into powder). The waterproof and breathable membrane is a composite membrane of a polytetrafluoroethylene porous membrane and a polyvinylidene fluoride porous membrane (manufacturer: Shanghai Minglie New Materials Co., Ltd., model: X2020), and the average pore size of the pores thereon is 0.2μm. The battery shell is made of ABS plastic, and the battery shell is sealed with the air electrode and the waterproof breathable membrane during one-piece injection molding to form a sealed battery cavity. Before use, add 90mL of water to the aluminum-air battery, tighten the sealing cover on the water inlet, and shake the battery. The battery surface temperature is monitored to be 40°C, the battery shell does not expand, and the waterproof breathable membrane does not leak. The aluminum-air battery is heated at 10mW / cm 2 The battery is discharged at a low power density until it reaches 0.9V low voltage protection, and the discharge capacity is 48Ah.

[0021] Example 3

[0022] The aluminum electrode is a sheet of high-purity aluminum with a length*width=9cm*7cm and a thickness of 1mm. The air electrode is composed of a catalyst layer, a copper mesh and a gas diffusion layer stacked and pressed together, and is a sheet with a length*width=10cm*8cm. The catalyst layer is prepared by mixing manganese dioxide, carbon powder and 40% mass concentration polytetrafluoroethylene emulsion in a mass ratio of 1:5:3 and spraying and drying. The gas diffusion layer is prepared by mixing carbon powder and polytetrafluoroethylene in a mass ratio of 2:1 and hot pressing at 300 degrees Celsius. The solid electrolyte consists of 25g sodium hydroxide, 1.0g sodium stannate, 9g sodium oxalate and 8g deionized water (the preparation method of the solid electrolyte is: after mixing the four components, melt mixing at a high temperature of 150°C, cooling to room temperature and solidifying, and then mechanically crushing them into powder). The waterproof and breathable membrane is a composite membrane of a polytetrafluoroethylene porous membrane and a polyvinylidene fluoride porous membrane, and the average pore size of the pores thereon is 0.2μm (manufacturer: Shanghai Minglie New Materials Co., Ltd., model: X2020). The battery shell is made of ABS plastic, and the battery shell is sealed with the air electrode and the waterproof breathable membrane during one-piece injection molding to form a sealed battery cavity. Before use, add 90mL of water to the aluminum-air battery, tighten the sealing cover on the water inlet, and shake the battery. The battery surface temperature is monitored to be 44°C, the battery shell does not expand, and the waterproof breathable membrane does not leak. The above aluminum-air battery is heated at 10mW / cm 2The battery is discharged at a low power density until it reaches 0.9V low voltage protection, and the discharge capacity is 43Ah.

[0023] Comparative Example 1

[0024] The aluminum electrode is a sheet of high-purity aluminum with a length*width=9cm*7cm and a thickness of 1mm. The air electrode is composed of a catalyst layer, a copper mesh and a gas diffusion layer stacked and pressed together, and is a sheet with a length*width=10cm*8cm. The catalyst layer is prepared by mixing manganese dioxide, carbon powder and 40% mass concentration polytetrafluoroethylene emulsion in a mass ratio of 1:5:3 and spraying and drying. The gas diffusion layer is prepared by mixing carbon powder and polytetrafluoroethylene in a mass ratio of 2:1 and hot pressing at 300 degrees Celsius. The solid electrolyte consists of 25g potassium hydroxide and 1.2g sodium stannate (the preparation method of the solid electrolyte is: mechanically grinding and mixing the two components). The waterproof and breathable membrane is a composite membrane of a polytetrafluoroethylene porous membrane and a polyvinylidene fluoride porous membrane (manufacturer: Shanghai Minglie New Materials Co., Ltd., model: X1010), and the average pore size of the pores thereon is 0.1μm. The battery shell is made of ABS plastic, and the battery shell is sealed with the air electrode and the waterproof breathable membrane during one-piece injection molding to form a sealed battery cavity. Before use, add 90mL of water to the aluminum-air battery, tighten the sealing cover on the water inlet, and shake the battery. The battery surface temperature is monitored to be 85°C, the battery shell expands, and the electrolyte leaks out of the waterproof breathable membrane. The above aluminum-air battery is heated at 10mW / cm 2 The battery is discharged at a low power density until it reaches 0.9V low voltage protection, and the discharge capacity is 29Ah.

[0025] Comparative Example 2

[0026] The aluminum electrode is a sheet of high-purity aluminum with a length*width=9cm*7cm and a thickness of 1mm. The air electrode is composed of a catalyst layer, a copper mesh and a gas diffusion layer stacked and pressed together, and is a sheet with a length*width=10cm*8cm. The catalyst layer is prepared by mixing manganese dioxide, carbon powder and 40% mass concentration polytetrafluoroethylene emulsion in a mass ratio of 1:5:3 and spraying and drying. The gas diffusion layer is formed by mixing carbon powder and polytetrafluoroethylene in a mass ratio of 2:1 and hot pressing at 300 degrees Celsius. The solid electrolyte consists of 25g sodium hydroxide and 1.0g sodium stannate (the preparation method of the solid electrolyte is: mechanically grinding and mixing the two components). The waterproof and breathable membrane is a composite membrane of a polytetrafluoroethylene porous membrane and a polyvinylidene fluoride porous membrane (manufacturer: Shanghai Minglie New Materials Co., Ltd., model: X2020), and the average pore size of the pores thereon is 0.2μm. The battery shell is made of ABS plastic, and the battery shell is sealed with the air electrode and the waterproof breathable membrane during one-piece injection molding to form a sealed battery cavity. Before use, add 90mL of water to the aluminum-air battery, tighten the sealing cover on the water injection port, and shake the battery. The battery surface temperature is monitored to be 92°C, the battery shell expands, and the electrolyte seeps out of the waterproof breathable membrane. The above aluminum-air battery is discharged at a power density of 10mW / cm2 until the battery is under voltage protection, and the discharge capacity is 24Ah.

[0027] In the comparative example, after the aluminum-air battery is activated by adding water, the battery temperature rises significantly, the battery shell expands, and the battery leaks, resulting in a significant reduction in discharge capacity. In the embodiment using the improved solution, after adding water to activate, the battery surface temperature is not high, the battery does not expand or leak, and the discharge capacity is effectively extended.

Claims

1. A sealed alkaline aluminum-air battery activated by water, comprising a battery case, an aluminum electrode, and an air electrode, wherein the aluminum electrode is placed in the battery case, the air electrode is placed at a through hole on the side wall of the battery case, and the edges of the air electrode are sealed and connected to the surrounding wall of the battery case at the opening end of the through hole or the inner wall of the through hole, characterized in that: A water inlet is provided at the top of the battery shell, a sealing cover which can open and close the water inlet is provided on the water inlet, a through hole is provided at the top of the battery shell, a waterproof and breathable membrane is provided at the through hole, the waterproof and breathable membrane covers the through hole, the edges around the waterproof and breathable membrane are tightly connected with the surrounding walls of the battery shell at the opening end of the through hole or the inner wall of the through hole, and a solid electrolyte is filled in the battery shell.

2. The battery according to claim 1, characterized in that: The solid electrolyte includes four components, component 1 is potassium hydroxide, sodium hydroxide or a mixture of the two, component 2 is potassium stannate, sodium stannate or a mixture of the two, component 3 is one or more of ammonium nitrate, ammonium oxalate, ammonium sulfate, potassium nitrate, potassium oxalate, potassium bromide, sodium nitrate, sodium oxalate, sodium bicarbonate, calcium nitrate and calcium chloride, and component 4 is deionized water; The molar ratio of component 1 to component 2 is 1000:1 to 20:1, preferably 500:1 to 100:

1. The molar ratio of component 1 to component 3 is 10:1 to 1:1, preferably 8:1 to 2:

1. The molar ratio of component 1 to component 4 is 10:1 to 1:1, preferably 5:1 to 1:

1.

3. The battery according to claim 2, characterized in that: The preparation method of the solid electrolyte is as follows: after mixing the four components in the required proportion, melt-mixing at a high temperature of 110 to 200° C., cooling until solidified, and then mechanically crushing.

4. The battery according to claim 1, characterized in that: The waterproof breathable membrane is a multilayer composite membrane of a polytetrafluoroethylene porous membrane and one or more of a polyethylene porous membrane, a polypropylene porous membrane, a polyvinylidene fluoride porous membrane, and a polyethylene terephthalate porous membrane; the pore size distribution range is 0.01 μm to 10 μm, preferably 0.1 to 0.5 μm.

5. The battery according to claim 1, characterized in that: The aluminum electrode is one or more of aluminum or aluminum alloy, wherein the mass content of metal aluminum is greater than or equal to 95%; The air electrode comprises a stacked catalyst layer, a current collector and a gas diffusion layer.

6. The battery according to claim 1, characterized in that: The battery shell is a blend of one or more of ABS, polycarbonate, polypropylene, polyethylene, and nylon.

7. The battery according to claim 1 or 6, characterized in that: The battery shell and the air cathode, as well as the battery shell and the waterproof breathable membrane are bonded by epoxy resin or fixed together during the integral injection molding of the battery shell to form a sealed battery cavity.

8. The battery according to claim 1, characterized in that: The sealing cover is screwed onto the water filling port through threads.

Citation Information

Patent Citations

  • Portable high-efficiency aluminum-oxygen power battery and its manufacturing method

    CN107017411B

  • Salt battery

    CN101090168A

  • Zinc-air secondary battery

    CN103947036A

  • Aluminum / air cell electrolyte and applications thereof

    CN106887649A

  • Method for improving ionic conductivity of solid electrolyte of lithium battery

    CN110600799A